Efisiensi Teknis Usahatani Manggis di Kabupaten Tasikmalaya - Jakiyah, Ulpah; Umbara, Dona Setia; Fitriadi, Budhi Wahyu (Universitas Galuh, 2026)
Efforts to increase production and productivity have been carried out by the Agricultural Extension Agency (BPP) through POPT (Plant Organism Control Program).). One of them is the activity of increasing mangosteen production in the Sumberhejo Lestari Farmer Group, Tasikmalaya Regency. So it is necessary to observe the level of efficiency, the factors that affect the level of mangosteen production, and the causes of the inefficiency in mangosteen production. The analytical method in this study uses the stochastic frontier method with three steps. Step 1 constructs an estimate of the Cobb-Douglas production function. Step 2 Determination of factors and efficiency level of mangosteen using stochastic frontier. Then step 3 determines the source of inefficiency in mangosteen production activities. The results of this study indicate that the factors of mangosteen production activities include land area, number of trees, labor, organic fertilizer, NPK fertilizer, and production costs. the factors that influence mangosteen production activities are the number trees and land area at the 5% level of significance. This is because the mangosteen tree is an ancestral tree and it was not nursed from the start. The land area has a negative effect because there is no farmer effort in planting mangosteen. The level of technical efficiency in mangosteen farming activities is said to be efficient (81.6%). Sources indicating inefficiency are land ownership status and length of formal education.